Organele vamale – aspecte conceptuale: noţiune, competenţe legale şi principii de activitate - Erhan, Ianuș; Cârnaț, Teodor (My University, 2012)
In the context of market economy, the State performs the regulation of external economic activity in order to ensure economic security and national and public interests. The state administration activity on the regulation of external economic activity, It is performed in almost all countries of the world, but the volume, forms and methods, concrete purposes and tasks are determined by the State relying on its internal and external policy, and not least the customs policy of the State. Today it is universally recognized the fact that as one of the institutions of customs realization represents customs administrations, as part of the custom system. They differ from one State to another Depending on the organizational structure, commercial and customs policy that they practiced, but in most of the States in which they are organized, they have similar functions and are in a constant search of best practices in order to implement the activities in their work. The deployment of activity of customs administration reflects the achieve of very important purposes for our country’s customs policy, ensuring efficient use of instruments of customs control and the regulation for the exchange of goods on customs territory and outside it, protecting the internal market, stimulating the development of national economy, promoting organizational restructuring, and the other objectives of State policy. At the same time, scientific analysis of conceptual issues relating to customs administration such as: notion, legal skills and principles of activity presents itself as a priority in the field of research with a view to understanding the mechanism of activity of these organs of administration, of its role and prospects of development.